Efektifitas Pemungutan Pajak Reklame dan Kontribusinya terhadap Penerimaan Pajak Daerah di Kota Bandung - Arvian Triantoro (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2010)
The purpose of this study was to find answers to the level of effectiveness of tax collection billboards in the city of Bandung, and its contribution to local tax revenue, which in this era of regional autonomy, local governments are required to work to improve the local revenue, such as an increase in local tax revenue of which is tax billboard. Occurred in the field of acquisition advertisement tax in the city of Bandung is a contribution that can not be underestimated. But in practice that should not pay attention to the potential, for the preparation of the target based only on experience of previous years.Length of a study conducted in January 2007 until July 2007. Along with the problem and research objectives,  this  study  implemented  a   descriptive  analytical  method,  where   thismethod is used to provide a systematic description, actual and accurate statement of fact, only describing situations or events not to seek or explain relationships and did not test the hypothesis. Data collection techniques are direct observation, direct communication and documentary study.From the results of data analysis showed that the level of effectiveness of tax collection billboards in the city of Bandung in the year 2006 quite well, reaching 53.56%, then the rate of growth of Advertisement Tax during the last six years shows the average reaches 53.94% per annum. Potential that should be obtained by the city of Bandung to achieve Rp48.736.796.510 Advertisement Tax, Advertisement Tax in 2000 and contributions to the Local Tax for the year 2006 based on the realization reached 15.84%, while based on the potential that should be able to reach 29.77%